MANAGEMENT OF THE HEAD OF THE INTERNAL REGION IMPROVING THE CULTURE OF CONGREGATIONAL PRAYER IN ZAID BIN TSABIT REGION - Arifin, Samsul; Salim, Agus; Zubaidi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Congregational prayer is worship carried out by a group of people, at least two people, with the selection of an imam who is fluent in reading and has a good understanding of Islamic law. It is the Imam who stands in the front row, while the others are the makmum or followers. As far as the author is concerned, there is an interesting side when discussing the efforts and supporting factors that regional heads are trying to improve the culture of congregational prayer for students.This research uses a descriptive qualitative approach. Data collection techniques use observation, interviews and documentation techniques. For data analysis, Miles and Huberman's interactive model was used through the stages of data collection, data reduction, data presentation and drawing conclusions.The results of discussions on regional head management in improving the culture of congregational prayer in the Zaid bin Tsabit area show that regional heads implement various efforts, such as setting an example, providing motivation and religious activities, routine supervision. The implementation of these efforts has proven effective in increasing the participation of students in carrying out congregational prayers and strengthening social and spiritual ties in the Islamic boarding school environment. Evaluation can be done by looking at supporting and inhibiting factors. This research concludes that the active role and commitment of the head of the Sengat area is important in building a strong culture of congregational prayer in Islamic boarding schools, especially in the Zaid bin Tsabit area.